Radiotherapy for Hodgkin Lymphoma - Specht, Lena.; Yahalom, Joachim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book deals in detail with all aspects of the best practice in modern radiotherapy for Hodgkin lymphoma. It provides the background and rationale for the inclusion of radiotherapy in today$1 (Bs combined-modality approach, including special clinical situations such as Hodgkin lymphoma in children, in the pregnant patient, and in the elderly. Radiotherapy planning using state-of-the-art imaging, target definition, planning software, and treatment equipment is expounded in detail. Acute and long-term side effects of radiotherapy are analyzed, and the implications for modern radiotherapy approaches in Hodgkin lymphomas are explained.s
History of radiotherapy of Hodgkin$1 (Bs disease (now Hodgkin lymphoma) -- Background and rationale for radiotherapy in early stage Hodgkin lymphoma (HL) -- Background and rationale for radiotherapy in advanced stage HL -- Salvage therapy for relapsed and refractory HL -- Principles of chemotherapy in HL -- Management of lymphocyte predominant HL -- Pediatric HL, the rationale for radiation therapy -- The role of imaging in radiotherapy for HL -- Target definitions for HL - the involved node radiation field concept -- Traditional and modern techniques for radiation treatment planning -- Quality assurance of radiotherapy for HL -- Evaluation of response after radiotherapy for HL -- HL in special populations and rare localizations -- Acute and long-term complications of radiotherapy for HL -- Proton therapy for HL -- Future prospects for radiotherapy for HL.s
Keywords: Medicine; Radiotherapy; Hematology; Oncology; Medicine & Public Health; Radiotherapy; Oncology; Hematology